Human behavioral response to fluctuating automation reliability. (November 2022) - Hutchinson, Jack; Strickland, Luke; Farrell, Simon; Loft, Shayne
Abstract: Human perception of automation reliability and automation acceptance behaviours are key to effective human-automation teaming. This study examined factors that impact perceptions of automation reliability over time and the acceptance of automated advice. Participants completed a maritime vessel classification task in which they classified vessels (contacts) with the assistance of automation. In Experiment 1 automation reliability successively switched from high to low (or vice versa). In Experiment 2 automation reliability decreased by varying magnitudes before returning to high. Participants did not initially calibrate to true reliability and experiencing low automation reliability reduced future reliability estimates when experiencing subsequent high reliability. Automation acceptance was predicted by positive differences between participant perception of automation reliability and confidence in their own manual classification reliability. Experiencing low automation reliability caused perceptions of reliability and automation acceptance rates to diverge. These findings have important implications for training and adaptive human-automation teaming in complex work environments. Highlights: Perceived automation reliability did not calibrate with initial true reliability. Experiencing low reliability had durable negative effects on perceived reliability. Automation use increased if automation perceived more reliable than manual ability. Low reliability increased divergence between perceived reliability and acceptance.